Associated Risk of Death from Covid-19 Infection in Patients with Hypertensive Co-Morbidities - Nina Widyasari; Hari Basuki; Chatarina Umbul Wahjuni (Universitas Airlangga, 2021)
Background: The COVID-19 pandemic caused by the SARS-CoV-2 virus has left infected patients with comorbidities in severe and deadly conditions. Hypertension is a non-communicable disease (NCD) and is one of the most common comorbidities observed in COVID-19 patients. Purpose: This study aims to understand the relationship between hypertension and the risk of death through COVID-19. Method: The study employed a systematic review of journals. Journals and articles related to hypertension and COVID-19 were collected and analyzed. The inclusion criteria was COVID-19 articles pertaining to hypertensive patients, and the exclusion criteria was articles that did not use English as well as those that did not display full text. Result: Hypertension is a multifactorial disease. The presence of hypertension is often not realized by the sufferer. A COVID-19 infection can worsen the condition of the person and can cause damage to vital organs. The use of antihypertensive drugs of the angiotensin-converting enzyme inhibitor (ACEI) and the angiotensin receptor blocker (ARB) groups can be continued to be administered to hypertensive patients. There should be no cause for concern for these patients to develop COVID-19 infections by taking these drugs. Conclusion: The risk of developing hypertension is that it can cause organ damage and lead to various complications. The SARS-CoV-2 infection in people with hypertension as a comorbidity, could worsen the condition of the individual until death occurs. Thus, hypertension management is necessary to properly minimize the severity.